Peste Des Petits Ruminants (PPR) Virus Infections in Goats in the Eastern Anatolia of Turkey - Gurcay, Metin; Kizil, Omer; Baydar, Ersoy (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
In this study, a totally 98 materials were used consist of different samples such as blood, oro-nasal swap, lung, spleen and lymph node from goats (n=38) in the 28 flocks suspected the PPRV infection as clinically and macroscopic pathologic remarks. The goats that used in this study housed in the 11 different provinces of Eastern Anatolia. RT-PCR was used for the diagnosis of PPRV infection. PPRV nucleic acid was detected in 50 of 98 materials by RT-PCR. According to the results of RT-PCR, the PPRV nucleic acid was detected in 39.2% (11/28), 44.7% (17/38) and 45.4% (5/11) of the flocks, sampled animals and provinces in eastern anatolia, respectively. Diagnostic value of necropsy materials such as lymph node, spleen, lung and of clinical samples such as oro-nasal swap and blood were determined more valuable diagnostic materials in the diagnosis of PPRV infection by RT-PCR. Data showed that PPRV infections of the goats were widespread in the Eastern Anatolia region. Additionally, it is determined that RT-PCR is sensitive and reliable method in the diagnosis of PPRV infections.
Türkiye'nin do?u anadolu bölgesin'deki keçilerde peste des petits ruminants (PPR) virus enfeksiyonları
Keywords: Goat; PPR; RT-PCR